2007
DOI: 10.2353/jmoldx.2007.070032
|View full text |Cite
|
Sign up to set email alerts
|

Is Occult Lymph Node Disease in Colorectal Cancer Patients Clinically Significant?

Abstract: The clinical significance of micrometastasis of colorectal cancer (CRC) to regional lymph nodes remains controversial. In this review, we analyze publications that have evaluated the clinical significance of occult lymph node metastasis in CRC. An extensive literature search identified 19 publications that evaluated the clinical significance of micrometastatic CRC by various methods, including immunohistochemistry (IHC; n ‫؍‬ 13) and reverse transcription-polymerase chain reaction (RT-PCR, n ‫؍‬ 6). These stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
171
0
3

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(176 citation statements)
references
References 40 publications
2
171
0
3
Order By: Relevance
“…Today, the clinical staging according to the UICC classification depends on routine histopathological examination, which eventually is allied with immunohistochemistry. In other cancers, the situation is different [13,14]. We hope that introducing molecular methods will improve the assessment of PTC.…”
Section: Introductionmentioning
confidence: 99%
“…Today, the clinical staging according to the UICC classification depends on routine histopathological examination, which eventually is allied with immunohistochemistry. In other cancers, the situation is different [13,14]. We hope that introducing molecular methods will improve the assessment of PTC.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, multiple studies have demonstrated that there is an increased risk of recurrence associated with occult metastases in lymph node-negative colon cancer (7,24,25). In a systematic review with a cumulative sample size of 4,087 patients, Rahbari and colleagues reported that molecular detection of occult disease in regional nodes is associated with an increased risk of disease recurrence and poor survival in pN0 patients (25).…”
Section: Discussionmentioning
confidence: 99%
“…Although histopathology remains the standard paradigm, staging imprecision by conventional microscopy reflects methodological limitations [2,5,24]. Microscopic visualization is insensitive, with 7 a lower limit for detection of ~1 cancer cell in 200 normal cells [26].…”
Section: Staging Colorectal Cancermentioning
confidence: 99%
“…Colorectal cancer causes ~10% of cancer-related deaths in the U.S., with a mortality rate approaching ~50% [1][2][3]. Mortality reflects metastases: ~20% of colorectal cancer patients have unresectable disease at presentation (stage IV) and >30% will develop metastases during the course of their disease [2][3][4][5]. Surgery continues to have the greatest impact on survival.…”
Section: Introductionmentioning
confidence: 99%